2010
DOI: 10.1093/cercor/bhq185
|View full text |Cite
|
Sign up to set email alerts
|

Are Old Adults Just Like Low Working Memory Young Adults? Filtering Efficiency and Age Differences in Visual Working Memory

Abstract: While it is well known that working memory functions decline with age, the functional reasons for this decline are not well understood. A factor that has proven critical for general individual differences in visual working memory capacity is the efficiency of filtering irrelevant information. Here, we examine to what degree this factor is also responsible for age differences in working memory. Young and old participants performed a change-detection task where some items in the encoding display were marked as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
221
8
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(268 citation statements)
references
References 35 publications
36
221
8
3
Order By: Relevance
“…Typically, such a group has a mean age .60 years and, on average, ,16 years of education. Memory capacity is smaller for older adults than for undergraduate students (Jost et al 2011). Furthermore, estimates of visual working memory capacity in change-detection tasks are typically obtained by assessing performance after delays of 1 sec (e.g., 900 msec in Luck and Vogel 1997; average delay of 1.1 sec [average of 300, 900, and 2000 msec] in Eng et al 2005), and therefore do not provide suitable estimates of working memory capacity in tests given after delays of 4 sec or longer (as in the studies of Nichols et al 2006;Olson et al 2006a).…”
Section: Retention Of Familiar Visual Items (Single Faces and Colors)mentioning
confidence: 94%
“…Typically, such a group has a mean age .60 years and, on average, ,16 years of education. Memory capacity is smaller for older adults than for undergraduate students (Jost et al 2011). Furthermore, estimates of visual working memory capacity in change-detection tasks are typically obtained by assessing performance after delays of 1 sec (e.g., 900 msec in Luck and Vogel 1997; average delay of 1.1 sec [average of 300, 900, and 2000 msec] in Eng et al 2005), and therefore do not provide suitable estimates of working memory capacity in tests given after delays of 4 sec or longer (as in the studies of Nichols et al 2006;Olson et al 2006a).…”
Section: Retention Of Familiar Visual Items (Single Faces and Colors)mentioning
confidence: 94%
“…This theoretical proposition is supported by recent studies that observed a selective age deficit in the NeuroImage 60 (2012) [71][72][73][74][75][76][77][78][79][80][81][82] suppression of irrelevant information in particular during early stages of WM encoding (Gazzaley et al, , 2008. These studies suggest that inhibitory control of WM contents may not be disabled completely in older adults, but rather delayed in time (Jost et al, 2011;Zanto et al, 2010). In addition, the robustness of inhibitory mechanisms depends on the task difficulty and the individual performance level.…”
Section: Introductionmentioning
confidence: 99%
“…A specific impairment in suppressing distractor representations in older adults has been linked to reduced WMC (5). Typically distractors are presented either with the items to be remembered (encoding distraction, ED, e.g., 6,7) or while these items are held in mind (delay distraction, DD, e.g., 5,8). We recently highlighted a distinction between the effects of these two types of distraction in younger adults (9).…”
mentioning
confidence: 99%
“…Here we examine the well-known age-related reduction in WMC. Previous work has identified an age-related delay in ED filtering (7) and an early age-related deficit in DD suppression (8). We directly compare the age-related decline in ED and DD to assess whether an ability to ignore a distraction at encoding or at delay provides the best predictor of general WMC.…”
mentioning
confidence: 99%